In Silico Study of FDA-Approved Drugs on Leishmania infantum CYP51, a Drug Repositioning Approach in Visceral Leishmaniasis - Juan Diego Guarimata; Martin Lavecchia (Chemistry Proceedings, 2024)
The main priority in leishmaniasis-endemic countries is to find safer and more accessible treatments for this neglected disease. In this study, we focus on a drug repositioning strategy using molecular docking. New molecular entities (NMEs) approved by the FDA from 2019 to the present were analyzed. The therapeutic target was the sterol 14-alpha demethylase from Leishmania infantum. Of the 125 NMEs tested, 16 demonstrated greater affinity in virtual screening than the co-crystallized inhibitor (fluconazole). This approach offers a promising method for identifying new uses for existing drugs and provides a rapid way to discover safer treatments for leishmaniasis.